Islamic Educational Strategies in Minimizing the Negative Impact of Polygamy on Family Mental Health: A Study in Glondong Village, Sawo, Yogyakarta - Hafidz, Hafidz; Latifatul Inayati, Nurul; Nashihin, Husna (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research is motivated by the increasing number of husbands engaging in polygamy, which leads to problems within their households. Various issues have been identified and explored in this study, including the positive and negative impacts of polygamy on family mental health in Glondong Village, Sawo, Yogyakarta. These impacts include anxiety, anger, high emotions, paranoia, and psychosomatic disorders. Factors contributing to the occurrence of polygamy in families in Glondong Village include infertility, the husband working outside the region, chronic illness of the wife, and a lack of affection from the husband towards the wife. The research problem is focused on understanding the effects of polygamy on family mental health in Glondong Village, as well as the factors leading to polygamy in these families. The objective of the study is to identify the impact of polygamy on family mental health and the factors leading to its occurrence. The research employs a descriptive qualitative method to depict the phenomena, utilizing informants such as the village head, polygamous husbands, their wives, and neighbors. Data collection methods include observation, interviews, and documentation. Data analysis is conducted using qualitative techniques, including data validation methods such as prolonged engagement, researcher persistence, and triangulation. The study finds that, negative impacts include hostility, lack of marital harmony, anxiety, irritability, high emotions, paranoia, and psychosomatic disorders. Factors contributing to polygamy include the husband's duty away from home, the wife's infertility or inability to bear children, chronic illness of the wife, and the husband's lack of affection towards the wife.